Penile Prosthesis in Transgender Men after Phalloplasty - Rajveer S. Purohit; Marissa Kent; Miroslav L. Djordjevic (Indian Journal of Plastic Surgery)
A penile prosthesis can be successfully implanted after phalloplasty in transgender men to permit sexual intercourse. A prosthesis can be categorized as malleable or inflatable. The most common penile prosthesis implanted after masculinizing genital surgery is the inflatable prosthesis but this can be a challenging operation with high complication rates. Penile prosthesis in transgender patients differs from cis-patients in many respects but one critical difference is the absence of the tough, protective tunica of the corporal body to contain the prosthesis. This causes greater mobility of the prosthesis under the skin and increases the risk of migration and erosion of the device through the skin. In addition, to overcome the absence of a corpora cavernosa, the proximal portion of the prosthesis must be anchored to bone. Complications include injury to the urethra, vascular injury, skin breakdown, infection, device migration, device failure, extrusion, and erosion. There is no robust data on the use of penile prosthesis in transgender men with only multiple reports of small numbers of patients. While successful implantation can improve patients' quality of life, surgeons should counsel patients about the relatively high risk of the need for revision surgery.